2009
DOI: 10.1519/jsc.0b013e3181854b15
|View full text |Cite
|
Sign up to set email alerts
|

Acute Heart Rate, Blood Pressure, and RPE Responses During Super Slow vs. Traditional Machine Resistance Training Protocols Using Small Muscle Group Exercises

Abstract: Acute cardiovascular and perceptual responses to Super Slow resistance training (SS) are not well understood. This study compared blood pressure (BP), heart rate (HR), and ratings of perceived exertion (RPE) between SS and traditional machine (TM) protocols. Participants (n = 20) completed three sessions of elbow flexion (EF) and knee extension (KE). Session 1 consisted of determining 1RM for EF and KE and a familiarization trial for the SS technique. Sessions 2 and 3 were counterbalanced, with subjects comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 10 publications
4
14
2
5
Order By: Relevance
“…A purposely slow resistance exercise training session such as used in the present study requires lifting external loads between 25-50% 1 RM [10,12,13,20,24]. In cases where high power, strength, and speed is required, as in sports, athletes need to be able to produce high levels of muscle force and power, and high contraction velocities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A purposely slow resistance exercise training session such as used in the present study requires lifting external loads between 25-50% 1 RM [10,12,13,20,24]. In cases where high power, strength, and speed is required, as in sports, athletes need to be able to produce high levels of muscle force and power, and high contraction velocities.…”
Section: Discussionmentioning
confidence: 99%
“…The slow velocity protocol used 28% of 1 RM loads for the high-bar parallel back squat, followed by the barbell bench press exercise, as suggested from previous controlled velocity studies and pilot work in our laboratory that indicated this intensity was the maximum that could be lifted for 10 repetitions [10,12,24]. The slow velocity protocol also used 1 set of 10 repetitions at a 10 sec eccentric, 10 second concentric tempo with no rest between repetitions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Os benefícios e adaptações decorrentes deste tipo de exercício são decorrentes de uma série de variáveis, tais como número de séries (Galvão & Taaffe, 2004), número de repetições (Shimano et al, 2006), frequência semanal (Burt, Wilson, & Willardson, 2007), tempo de intervalo entre as séries e sessões de treino (Willardson & Burkett, 2008), intensidade e volume de treino (Prestes, De Lima, Frollini, Donatto, & Conte, 2009), tipo de acções musculares (Blazevich, Cannavan, Coleman, & Horne, 2007), ordem dos exercícios (Gentil, Oliveira, De Araújo, Do Carmo, & Bottaro, 2007) e velocidade de movimento (Wickwire, McLester, Green, & Crews, 2009). Com isso, o treinador ou preparador físico, conhecendo os diferentes tipos de treino, pode otimizar o condicionamento físico de seus atletas para determinada modalidade desportiva (Carpinelli, Otto, & Winett, 2004;Peterson, Rhea, & Alvar, 2005).…”
Section: W Materko M Duarte El Santos Hs Juniorunclassified
“…Assim, uma constante resposta reflexa e adrenérgica, medida pelo sistema simpático aumentaria a PA para vencer essa pressão mecânica e manter o fluxo. Portanto, parece que o aumento da intensidade do protocolo de TF deveria ser diretamente proporcional ao aumento da PA. Porém, as respostas são controversas, pois existem estudos demonstrando que a maior intensidade do protocolo de TF resulta em maior (WERBER-ZION, GOLDHAMMER, SHAAR e POLLOCK, 2004;WICKWIRE et al, 2009;SOUSA et al, 2010), menor (FLECK e DEAN, 1987;LAMOTTE et al, 2005;CASTINHEIRAS-NETO et al, 2010;NERY et al, 2010) ou não altera o estresse cardiovascular (MEYER et al, 1999;KING, DRACUP, FONAROW e WOO, 2000). Alguns desses estudos tiveram o seu protocolo analisado na TABELA 2 e observa-se que a densidade não está equalizada.…”
Section: A Manipulação Das Variáveis Independentes Dos Protocolos Deunclassified